THE ENTHUSIASTIC EFFECT OF SHAHIBUL MAAL TO SAVING AT THE WONOGIRI SHARIAH SYARIAH COOPERATIVE - Lia Puspitasari; Eko Meiningsih Susilowati; Tri Widianto (ADVANCE, 2018)
The purpose of this study is to determine the factors that influence the interest of shahibul maal to save in the Sharia Cooperative Permata. Analytical technique in this research consist of instrument test: validity test and reliability test, classical assumption test, multiple linear regression analysis, t test, and R² test. Based on the results of this study can be seen that the trust, quality of service and religiulitas positively affect the interest of shahibul maal to save in sharia cooperative. Result of t test show that trust, service quality and religiulity have positive and significant effect to interest of shahibul maal to save in syariah cooperative. Adjusted R square test results obtained results of 0.418 which means the variability of interest shahibul maal to save in cooperatives can be explained by the variable trust, service quality and religiulity 41.8% while the remaining 58.2% explained by other variables that do not participate observed. For example processes, people and products etc. The most dominant variable affecting the interest of shahibul maal to save in sharia cooperative is trust, hence effort to increase interest of shahibul maal to save in syariah cooperative need to emphasize trust, through socialization and various activities.Keywords: trust, quality of service, religiulitas and Interests shahibul maal to save.